Project management - Maylor, Harvey
Combining a strong academic approach with relevant practical cases, this text skillfully shows the range of issues that face project managers throughout the project cycle. This new Media Edition comes with a free CD Rom containing a 60 day trial version of Microsoft Project for students. This edition is easier to use than ever before, with two colour text design and more diagrams and figures to aid navigation and understanding. Project Management is used extensively to accompany courses on undergraduate, masters and MBA programmes, as well as for in-company training and for professionals wanting to bring themselves up-to-date with developments in the field.